Health workers' views on factors affecting caregiver engagement with bubble CPAP - Sangwani Salimu; Mai-Lei Woo Kinshella; Marianne Vidler; Mwai Banda; Laura Newberry; Queen Dube; Elizabeth M. Molyneux; David M. Goldfarb; Kondwani Kawaza; Alinane Linda Nyondo-Mipando (BMC, 2020)
Abstract Background Severe respiratory distress is a leading cause of mortality among neonates in Malawi. Despite evidence on the safety, cost effectiveness and efficacy of bubble continuous positive airway pressure (CPAP) in managing the condition, its use in Malawian health facilities is limited and little is known about caregivers' engagement with perspectives of bubble CPAP. The purpose of this study was to explore caregiver perspectives for bubble CPAP at both central and district hospitals and key factors that enable effective caregiver engagement in Malawi. Methods This was a descriptive qualitative study employing secondary analysis of 46 health care worker in-depth interviews. We interviewed the health workers about their thoughts on caregiver perspectives regarding use of bubble CPAP. We implemented the study at a tertiary facility and three district hospitals in southern Malawi. This was a part of a larger study to understand barriers and facilitators to implementing neonatal innovations in resource-constrained hospitals. Interviews were thematically analysed in NVivo 12 software (QSR International, Melbourne, Australia). Health workers were purposively selected to include nurses, clinicians and district health management involved in the use of bubble CPAP. Results Emerging issues included caregiver fears around bubble CPAP equipment as potentially harmful to their new-borns and how inadequate information provided to caregivers exacerbated knowledge gaps and was associated with refusal of care. However, good communication between health care providers and caregivers was associated with acceptance of care. Caregivers' decision-making was influenced by relatives and peer advocates were helpful in supporting caregivers and alleviating fears or misconceptions about bubble CPAP. Conclusions Since caregivers turn to relatives and peers for support, there is need to ensure that both relatives and peers are counselled on bubble CPAP for improved understanding and uptake. Health workers need to provide simplified, accurate, up-to-date information on the intervention as per caregivers' level of understanding. Notably, contextualised comprehensible information will help alleviate caregivers' fear and anxieties about bubble CPAP.